Investigation on the Variability of Simulated and Observed Ground Motions for Bucharest Area. Issue 10 (26th November 2018) - Pavel, Florin
ABSTRACT: In this research, we evaluate the variability of ground motions from Vrancea intermediate-depth earthquakes for Bucharest area. In the first step of the analysis, the variability of ground motions recorded during four intermediate-depth Vrancea seismic events is assessed. Subsequently, the variability of ground motions simulated using the stochastic method is evaluated. The soil conditions in Bucharest are taken into consideration using the horizontal-to-vertical spectral ratios computed from the ground motions recorded during Vrancea seismic events with magnitudes MW ≤ 6.0. The stochastic simulations are performed for earthquakes with magnitudes in the range MW = 5.5–7.5 and four focal depths (90, 110, 130, and 150 km), while the epicentral positions take into account the instrumental seismicity of the 20th century. The results show similar mean normalized acceleration response spectra for the 13 analyzed sites in Bucharest area, as well as a significant influence of the earthquake magnitude on the spectral shapes. A comparison of the simulated ground motions with the amplitudes obtained from a ground motion model derived for the Vrancea subcrustal seismic source shows much larger spectral amplitudes for the former category. In addition, the largest part of the ground motion variability can be attributed to earthquake magnitude.